2018
DOI: 10.1016/j.neurobiolaging.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem MRI and histology demonstrate differential iron accumulation and cortical myelin organization in early- and late-onset Alzheimer's disease

Abstract: Previous MRI studies reported cortical iron accumulation in early-onset (EOAD) compared to late-onset (LOAD) Alzheimer disease patients. However, the pattern and origin of iron accumulation is poorly understood. This study investigated the histopathological correlates of MRI contrast in both EOAD and LOAD. T2*-weighted MRI was performed on postmortem frontal cortex of controls, EOAD, and LOAD. Images were ordinally scored using predefined criteria followed by histology. Nonlinear histology-MRI registration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 51 publications
18
104
0
Order By: Relevance
“…Another possibility is remyelination (Peters, ), which has also been suggested by a recent study by Bulk et al (). Using a combined post mortem T2*w MRI with histology, the authors showed an unexpected increase in cortical myelin staining in late stage AD (Bulk et al, ). The increase in myelin density did show a more disorganized cortical myelin architecture compared to controls.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Another possibility is remyelination (Peters, ), which has also been suggested by a recent study by Bulk et al (). Using a combined post mortem T2*w MRI with histology, the authors showed an unexpected increase in cortical myelin staining in late stage AD (Bulk et al, ). The increase in myelin density did show a more disorganized cortical myelin architecture compared to controls.…”
Section: Discussionmentioning
confidence: 61%
“…Note however, that Bulk et al (2018), and multiple other studies (Ayton et al, 2019;Connor, Snyder, Beard, Fine, & Mufson, 1992;Ward, Zucca, Duyn, Crichton, & Zecca, 2014;Zecca, Youdim, Riederer, Connor, & Crichton, 2004), also demonstrated increased iron accumulation in AD. T2-w sequences are known to be highly sensitive to iron deposits, and so the T1-w/T2-w ratio may reflect the presence of both processes (Dusek, Dezortova, & Wuerfel, 2013).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Iron levels in the brain accumulate with age (Aquino et al, 2009), which may engender risk of disease. In AD, cortical iron levels are elevated beyond the already high levels that occur during age, as measured by various methods in post-mortem tissue (Andrasi, Farkas, Scheibler, Reffy, & Bezur, 1995;Bulk et al, 2017;Bulk et al, 2018;Collingwood et al, 2005;Connor, Menzies, St Martin, & Mufson, 1992;De Reuck et al, 2014;Duce et al, 2010;Galazka-Friedman et al, 2011;Goodman, 1953;Hallgren & Sourander, 1960;Smith et al, 2010;Smith, Harris, Sayre, & Perry, 1997;van Duijn et al, 2017).…”
Section: Iron Pathology In Admentioning
confidence: 99%
“…Although cholesterol in myelin is a major determinant of T1-weighted signal intensity 69,70 , so in part is iron, water content and dendrite density [71][72][73] . While cortical GM intensity corresponds closely with histologically based myelin profiles 74 , GWC is microstructurally complex and a product of GM and WM.…”
Section: Exploratory Analyses On the Associations Between Pgs For Neumentioning
confidence: 99%